(untitled) (Journal of the College of Basic Education, 2023)
In recent years, educators have paid increasing attention to activities and events that make the student the focus of the teaching and learning process. The most prominent of these activities is the use of the cooperative learning method. A picture of a group project, then the teacher and the students plan together, assigning each individual in the group a specific task, and the teacher directs the students to various sources and provides them with meaningful activities, then the students analyze the information and it is presented in the class, and the evaluation is done by the students themselves, as the groups evaluate each other under the supervision of the teacher.